Metabolic and physiological regulation of Chlorella sp. (Trebouxiophyceae, Chlorophyta) under nitrogen deprivation - Yong, Wai Kuan; Lim, Phaik Eem; Vello, Vejeysri; Sim, Kae Shin; Majid, Nazia Abdul; Mustafa, Emienour Muzalina; Sulaiman, Nik Meriam Nik; Liew, Kan Ern; Chen, Brenna Jia Tian; Phang, Siew Moi (Science Press, 2019)
A freshwater green microalgae Chlorella sp., UMACC344 was shown to produce high lipid content and has the potential to be used as feedstock for biofuel production. In this study, photosynthetic efficiency, biochemical profiles and non-targeted metabolic profiling were studied to compare between the nitrogen-replete and deplete conditions. Slowed growth, change in photosynthetic pigments and lowered photosynthetic efficiency were observed in response to nitrogen deprivation. Biochemical profiles of the cultures showed an increased level of carbohydrate, lipids and total fatty acids, while the total soluble protein content was lowered. A trend of fatty acid saturation was observed in the nitrogen-deplete culture with an increase in the level of saturated fatty acids especially C16:0 and C18:0, accompanied by a decrease in proportions of monounsaturated and polyunsaturated fatty acids. Fifty-nine metabolites, including amino acids, lipids, phytochemical compounds, vitamins and cofactors were significantly dysregulated and annotated in this study. Pathway mapping analysis revealed a rewiring of metabolic pathways in the cells, particularly purine, carotenoid, nicotinate and nicotinamide, and amino acid metabolisms. Within the treatment period of nitrogen deprivation, the key processes involved were reshuffling of nitrogen from proteins and photosynthetic machinery, together with carbon repartitioning in carbohydrates and lipids.